Kadar Fenolik Dan Flavonoid Total Dalam Ekstrak Metanol Daun Cemba (Acacia rugata (Lam.) Fawc. Rendle) - Andi Amaliah Dahlia; Nur Qadri Amima; Aulya Rachma Arum; Rezki Amriati Syarif; Aktsar Roskiana Ahmad (Jurnal Fitofarmaka Indonesia, 2022)
This study aims to determine and compare the phenolic and flavonoid content of methanol extract in Acacia rugata (Lam.) Fawc. Rendle leaves using UV-Vis spechtrophotometer and TLC-densitometry. The Acacia rugata (Lam.) Fawc. Rendle extracted by using maceration applied sonicator. The quantitative analysis measured by UV-Vis spectrophotometer at wavelength 430 nm. The TLC–densitometry performed at wavelength of 254 nm and quercetin was as a standard. The results showed that the phenolic total showed 0.506 gGAE/g extract and 0.879 gGAE/g extract. The flavonoid total showed 0.44 gQE/g extract and 0.73 gQE/mg extract respectively.